High Efficiency Generalized Parallel Counters for Look-Up Table Based FPGAs. (19th October 2015) - Khurshid, Burhan; Mir, Roohie Naaz
Abstract : Generalized parallel counters (GPCs) are used in constructing high speed compressor trees. Prior work has focused on utilizing the fast carry chain and mapping the logic onto Look-Up Tables (LUTs). This mapping is not optimal in the sense that the LUT fabric is not fully utilized. This results in low efficiency GPCs. In this work, we present a heuristic that efficiently maps the GPC logic onto the LUT fabric. We have used our heuristic on various GPCs and have achieved an improvement in efficiency ranging from 33% to 100% in most of the cases. Experimental results using Xilinx 5th-, 6th-, and 7th-generation FPGAs and Stratix IV and V devices from Altera show a considerable reduction in resources utilization and dynamic power dissipation, for almost the same critical path delay. We have also implemented GPC-based FIR filters on 7th-generation Xilinx FPGAs using our proposed heuristic and compared their performance against conventional implementations. Implementations based on our heuristic show improved performance. Comparisons are also made against filters based on integrated DSP blocks and inherent IP cores from Xilinx. The results show that the proposed heuristic provides performance that is comparable to the structures based on these specialized resources.